Formation of foreign language writing skills based on formative assessment technology (B1 level) (Journal of Educational Sciences, 2021)
The article discusses the features of the formation of students ‘ skills of writing a foreign language at the level of B1. Writing skills arose on the basis of the sound speech of the human race, as a mirror of the culture and traditions of each country, in the knowledge and accumulated experience of the individual. It plays an important role in teaching a foreign language This article differentiates the effectiveness of formative assessment technology as a way of mastering writing skills in a foreign language.Information was provided on the role of writing skills and their features, which are important when teaching a foreign language. In addition, the article shows the mechanism of improving teaching and learning – the im- portance of formative assessment in the educational process and the types of technologies of formative assessment, ways of its application. Shown the goals of the components of formative assessment used to measure progress, the level of learning by students in a daily lesson. When assessing students based on the technology of formative assessment, different forms of assessment are used: peer assessment, self-assessment, group assessment. The results of the study revealed the impact of the use of formative assessment on the improvement of writing skills in a foreign language and the effectiveness of various methods used in this context.Key words: language, writing skills, foreign language, formative assessment, technology, writing, speech, level, rule.